DESCRIPTION OF THE DISEASE STRUCTURE, TREATMENT RESULTS AND SOME RELATED FACTORS OF PATIENTS IN THE DEPARTMENT OF UPPER LIMBS SURGERY AND MICROSURGERY INSTITUTE OF TRAUMA AND ORTHOPEDICS 108 MILITARY CENTRAL HOSPITAL IN 5 YEARS FROM 2017 TO 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the current status of disease structure, treatment results and some related factorsof patients in the Department of Upper Limbs Surgery and Microsurgery Institute of Trauma andOrthopedics, 108 Military Central Hospital in 05 years from 2017 to 2021 and recommend innovativesolutions to help guide and develop a development plan for the Department of Upper Limbs Surgeryand Microsurgery, 108 Military Central Hospital. Research methodology Research: Using a crosssectional descriptive study method on 9,730 patients admitted to the Department of Upper LimbsSurgery and Microsurgery at the Institute of Trauma and Orthopedics, 108 Military Central Hospitalfor 5 years from 2017 to 2021. Results: The rate of patients entering treatment was divided into 04 agegroups, in which the concentration was mainly in the age group from 16-59 years old, respectively, therates from 2017 to 2021 were > 70% respectively. The incidence of the disease in men over the yearsis higher than in women. The percentage of inpatients using health insurance cards tends to increasegradually over the years and peaks in 2021 with the rate of 85.08%. The proportion of patients inthe group with indications for surgical treatment tended to increase gradually, respectively: 76.87%;86.27%%; 89.49%; 88.59%; 88.27%. The total rate of type I and special type surgery is over 60%. Theaverage treatment day tends to decrease over the years, the maximum average is 13 days and the lowestaverage is 11 days. In which, the focus is mainly on the group with a hospital stay of 6 to 10 days with arate of 44.46%. The rate of recovery, relief and reduction when there is indication to be discharged in 05years are over 96%, respectively: 97.42%; 96.17; 98%; 97.74%; 97.4% and the mortality rate tends todecrease. Conclusion: The proportion of patients admitted to hospital for treatment is mainly in the 16-59 age group. In all 05 years, the highest proportion is the group with indications for surgical treatment,focusing mainly on type I surgery and especially, the rate is > 60%. The rate of recovery and reliefwhen indicated for hospital discharge accounted for over 96%, only the 5-year mortality rate ≤ 0.04%.
Keywords: Disease model, treatments situation, Department of Upper Limbs Surgery and Microsurgery, Institute of Trauma and Orthopedics, 108 Military Central Hospital.